Innovative Potential of Photobook Format in Ethnocultural Communication - Elena S. Doroschuk (Publishing house "Sreda", 2020)
The features of such a widely used format as a photo book in the context of visual ethnography were reviewed in the article. It is noted that the photobook is studied as a tool for creating visual ethnographic materials that allow to conduct a research on modern cultures and ethnic groups to form a cultural identity. Methods. As the subject of analysis, modern photobooks created by the photographer from Japan Ikuru Kuwajima were selected. Results. The potential of the photobook as an author's work is revealed and its communicative potential in ethnocultural interaction is described. An ethno-photo book is defined as a format of visual communication in which each photograph has an ethnical meaning, which contributes to the creation of author's photo narration, as a specific form of reflection of an ethnos, with a representation of ethnic images. The special functions of the ethno-photo book, which are realized upon activation of the author's principle, are highlighted: the search for their own identity; pictorial (plot) narrative about an ethnic group; creating the integrity of ethno-narration; increment of information about the ethnic group; ethnos research by means of a photo image; details of the ethnic world view; preservation of ethnic pictures of the world; comprehending the culture of another. It has been determined that a modern photo book is distinguished by documentary content and multimedia features that give its content traits of pragmatism and streaming. An ethno-photo book is manifested as a meaningful substantial work in which the author narrates a pictorial story about an ethnos through photographs, creating a holistic artistic and semantic image of the ethnos. It is concluded that all this contributes to a special emphasis of the reader on certain elements of the ethnographic image and contributes to the creation of new information about the ethnos. It is mentioned that one of the varieties of photobooks is the author's photobook, as an in-depth study of oneself in the context of the ethnicity of the territories reflected in the photo-chronicles of the photographer.